2014
DOI: 10.1098/rsos.140066
|View full text |Cite
|
Sign up to set email alerts
|

Viewing images of snakes accelerates making judgements of their colour in humans: red snake effect as an instance of ‘emotional Stroop facilitation’

Abstract: One of the most prevalent current psychobiological notions about human behaviour and emotion suggests that prioritization of threatening stimuli processing induces deleterious effects on task performance. In order to confirm its relevancy, 108 adults and 25 children were required to name the colour of images of snakes and flowers, using the pictorial emotional Stroop paradigm. When reaction time to answer the colour of each stimulus was measured, its value was found to decrease when snake images were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
(56 reference statements)
3
11
0
Order By: Relevance
“…Similar experiments reported in the past have consistently shown that detection of a tilted straight line target among vertical straight line distractors is easier than vice versa, and that detection of a snake among flower distractors is easier than vice versa. This contrasting pattern for the two related tasks is known as a “search asymmetry” effect (Treisman and Souther, 1985; Treisman and Gormican, 1988) and was again confirmed by the present study in children both with and without autism.…”
Section: Discussionsupporting
confidence: 88%
“…Similar experiments reported in the past have consistently shown that detection of a tilted straight line target among vertical straight line distractors is easier than vice versa, and that detection of a snake among flower distractors is easier than vice versa. This contrasting pattern for the two related tasks is known as a “search asymmetry” effect (Treisman and Souther, 1985; Treisman and Gormican, 1988) and was again confirmed by the present study in children both with and without autism.…”
Section: Discussionsupporting
confidence: 88%
“…A 22‐inch monitor connected to a personal computer was placed on a table. An adapted single‐trial version of the pictorial emotional Stroop task (Constantine et al., ; Shibasaki et al., ; 9 was used in the present experiment. Participants were told by an experimenter, who had not been notified about the purpose of this study, that they would see a series of color‐filtered images, and they were instructed to indicate the color of each image as quickly as possible via a key‐press, while ignoring the content of each image.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between keypad position and color was counterbalanced across the participants. More detailed information about the protocol has been provided elsewhere (Shibasaki et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations